2006
DOI: 10.1128/aem.00344-06
|View full text |Cite
|
Sign up to set email alerts
|

Capture and Retention of Cryptosporidium parvum Oocysts by Pseudomonas aeruginosa Biofilms

Abstract: The association of Cryptosporidium oocysts with biofilm communities can influence the propagation of this pathogen through both environmental systems and water treatment systems. We observed the capture and retention of C. parvum oocysts in Pseudomonas aeruginosa biofilms using laboratory flow cells. Biofilms were developed in two different growth media using two different strains of P. aeruginosa, a wild-type strain (PAO1) and a strain that overproduces the exopolysaccharide alginate (PDO300). Confocal laser-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
58
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 48 publications
2
58
0
Order By: Relevance
“…In the present study, summer biofilms were the only biofilms that were significantly different in thickness, but their thicker biomass did not yield an increase in the number of oocysts attached to the biofilm (Table 1). Although not significant, a trend of increasing oocyst attachment with increasing surface roughness (measured as the standard deviation of biofilm thickness measurements) was observed, as seen by others using 1-m microbeads (5) and C. parvum oocysts (23). In addition, the experimental conditions (specifically, experimental temperature) did not appear to impact oocyst attachment to the biofilms either (Fig.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…In the present study, summer biofilms were the only biofilms that were significantly different in thickness, but their thicker biomass did not yield an increase in the number of oocysts attached to the biofilm (Table 1). Although not significant, a trend of increasing oocyst attachment with increasing surface roughness (measured as the standard deviation of biofilm thickness measurements) was observed, as seen by others using 1-m microbeads (5) and C. parvum oocysts (23). In addition, the experimental conditions (specifically, experimental temperature) did not appear to impact oocyst attachment to the biofilms either (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…The quick steady-state deposition of particles has been found to be independent of cell density in the biofilm or biofilm thickness, but dependent on the particle surface properties (i.e., surface charge and hydrophobic properties) and the physical properties of the biofilm (i.e., surface roughness and pore size) (12,23). Accordingly, biofilm thickness did not appear to play a role in how many oocysts attached to the biofilms in the present study, as also shown by others (5,12,16,17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations